The bHLH Transcription Factor HBI1 Mediates the Trade-Off between Growth and Pathogen-Associated Molecular Pattern–Triggered Immunity in Arabidopsis . Issue 2 (18th February 2014) - Fan, Min; Bai, Ming-Yi; Kim, Jung-Gun; Wang, Tina; Oh, Eunkyoo; Chen, Lawrence; Park, Chan Ho; Son, Seung-Hyun; Kim, Seong-Ki; Mudgett, Mary Beth; Wang, Zhi-Yong
Abstract : HBI1 is activated posttranscriptionally by growth-promoting hormonal and environmental signals through the triple-HLH/bHLH cascade but is repressed transcriptionally by pathogen-associated molecular pattern signals. HBI1 both activates growth and inhibits immunity, thereby acting as a crosstalk node that mediates the trade-off between growth and immunity. Abstract: The trade-off between growth and immunity is crucial for survival in plants. However, the mechanism underlying growth-immunity balance has remained elusive. The PRE-IBH1-HBI1 tripartite helix-loop-helix/basic helix-loop-helix module is part of a central transcription network that mediates growth regulation by several hormonal and environmental signals. Here, genome-wide analyses of HBI1 target genes show that HBI1 regulates both overlapping and unique targets compared with other DNA binding components of the network in Arabidopsis thaliana, supporting a role in specifying network outputs and fine-tuning feedback regulation. Furthermore, HBI1 negatively regulates a subset of genes involved in immunity, and pathogen-associated molecular pattern (PAMP ) signals repress HBI1 transcription. Constitutive overexpression and loss-of-function experiments show that HBI1 inhibits PAMP -induced growth arrest, defense gene expression, reactive oxygen species production, and resistance to pathogen. These results show that HBI1, as a component of the central growth regulation circuit, functions as a major node of crosstalk that mediates a trade-off between growth and immunity in plants.